2019
DOI: 10.22435/sel.v6i2.1651
|View full text |Cite
|
Sign up to set email alerts
|

Simulasi Docking Senyawa Aktif Daun Binahong Sebagai Inhibitor Enzyme Aldose Reductase

Abstract: The metabolic syndrome is the cause of death around the world caused by diabetic mellitus. Binahong leaf is a kind of plant that is widely used to treat various diseases. This study aims to investigate the inhibitory activity of binahong leaves compound in inhibiting the aldose reductase which has role of converting glucose into sorbitol by docking simulation. The compound of binahong leaves consists of ursolic acid, vitexin, and oleonolic acid (ligand testing). These compound were taken from PubChem site, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 0 publications
0
11
0
9
Order By: Relevance
“…To determine whether a compound was predicted to have better activity, a comparison drug compound was used as a control. The test compound that has a lower affinity value than the comparison compound is predicted to have a more stable binding ability than the comparison compound (Suhadi et al 2019). In addition, the interaction of amino acid residues determines whether the compound has the same biological activity as the comparison or native ligand (Prasetiawati et al 2021).…”
Section: Ligand-receptor Binding Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether a compound was predicted to have better activity, a comparison drug compound was used as a control. The test compound that has a lower affinity value than the comparison compound is predicted to have a more stable binding ability than the comparison compound (Suhadi et al 2019). In addition, the interaction of amino acid residues determines whether the compound has the same biological activity as the comparison or native ligand (Prasetiawati et al 2021).…”
Section: Ligand-receptor Binding Resultsmentioning
confidence: 99%
“…In general, the binding between the drug-receptor was reversible, so the drug would leave the receptor immediately when the drug level in the extracellular fluid decreased. The bonds involved in drug and receptor interactions must be relatively weak but still strong enough to compete with other bonds (Suhadi et al 2019). Therefore, most of the docking results do not find any covalent bonds because covalent bonds are irreversible even though they produced strong affinity and stable interactions (Prasetiawati et al 2021).…”
Section: Ligand and Receptor Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis results showed that wild-type receptors had 89.4% residues in quadrant I, 10.4% residues in quadrant II, 0.2% residues in quadrant III, and 0% residues in quadrant IV (Figure 3). A good quality model or structure is expected to have more than 80% residues in the most favored region and less than 1% non-glycine residues in disallowed regions [42]. The 3D model of the wild-type receptor that has been made has good quality because there are more than 80% residues in the most favored region.…”
Section: Ipbcc08610 God Structurementioning
confidence: 99%
“…The stability of the compound can be seen from its low binding energy. The lower the binding energy and the stronger noncovalent interactions may affect more spontaneous reactions between ligands and proteins (Suhadi, Rizarullah, and Feriyani 2019). Epicatechin-3-O-Gallate can be a candidate for COX-2 inhibitor and its strength is much higher when compared to Gallocatechin and Tamarixetin.…”
Section: Docking Validationmentioning
confidence: 99%